Modality and Discursive Strategies in United Nations Security Council Resolutions: A Sociolinguistic Analysis - Kuchimova, Nilufar Turanbayevna (The Lingua Spectrum, 2026)
This article examines modality and discursive strategies in United Nations Security Council (UNSC) resolutions from linguistic and sociolinguistic perspectives. The study aims to identify how language functions as a mechanism of authority, regulation, and institutional power in legal-diplomatic discourse. The research material consists of UNSC resolutions and International Court of Justice decisions published between 2015 and 2017. The analysis is based on critical discourse analysis and functional approaches to modality (Fowler, 1991; Halliday, 1994). The findings demonstrate that UNSC resolutions are characterized by syntactic complexity, nominalization, passivization, and dense legal terminology. As well as, particular attention is paid to the modal verb shall, which functions as a performative marker of legal obligation and institutional authority. Comparative analysis of English and Uzbek texts reveals semantic expansion and translation transformations in Uzbek renderings. Moreover, the study confirms that UN discourse reflects and constructs global power relations through institutional language.